The Pengaruh Motivasi dan Efikasi Diri Terhadap Kinerja Akademik Mahasiswa Magister Dengan Manajemen Waktu Sebagai Variabel Moderasi - Hafizh Hidayatullah Esas (Politeknik Negeri Padang, 2021)
This research has the goal of testing the influence of motivation, self-efficacy, and time management asmoderation variables on the academic performance of master's students. The research method is acorrelational descriptive method that is obtained data analyzed to test the relationship between factors andvariables. The data analysis method used in this study is to use the SEM (Structural Equation Modeling)method. The type of Structure Equation Modeling (SEM) used is Smart PLS. Measurement consists of outermodel and inner model. Outer model measurements are carried out by means of validity tests and reliabilitytests. While the inner model measurement is done by means of R-Square test and hypothesis test. The resultsshowed that: 1) Motivation has a positive and significant influence on academic performance, 2) Self-efficacyhas a positive and significant influence on academic performance, 3) Time management has a positive andsignificant influence on academic performance, 4) Time management does not moderate the relationshipbetween motivation to academic performance, 5) Time management does not moderate the relationshipbetween efficacy to academic performance.